Offene Reposition und interne Fixation lateraler Tibiaplateaufrakturen mit freien subchondralen 2,7-mm-Schrauben = Open reduction and internal fixation of lateral tibial plateau fractures with free subchondral 2.7 mm screws - Reul, Maike; Johnscher, Franziska (Operative Orthopädie und Traumatologie, 2017)
ObjectivesExact reconstruction of the depressed articular surface and stable subchondral fixation of the lateral tibial plateau (ORIF, “open reduction and internal fixation”).IndicationsTibial plateau fractures with involvement of the lateral column and depression of the articular surface.ContraindicationsCritical soft tissue. Severe osteoporosis.Surgical techniqueSupine position, classical anterolateral approach, lateral submeniscal arthrotomy, visualisation of the fracture, osteotomy of the lateral tibial condyle. Reconstruction of the articular surface under visual control and temporary fixation with Kirschner wires. One or more 2.7 mm locking screws are placed subchondral for permanent stable fixation of the articular surface. If needed, the metaphyseal bone defect is filled with autologous or allogenic bone graft. The lateral tibial condyle is reduced and a 3.5 mm (variable angle) locking compression plate applied. Closure of fascia and skin in layers.Follow-up managementFree range of motion, in case of residual instability of the collateral ligaments varus-valgus stabilizing brace, partial weight-bearing of 10-15 kg for 8 weeks, control computed tomography (CT) scan after 3 months.ResultsSince February 2014, a total of 23 lateral tibial plateau fractures were treated using the described technique; 4 patients were lost to follow-up and the 3‑month follow-up of 2 patients is not completed yet. After an average of 167 days, 11 patients had no complaints. At approximately 3 months postoperatively, 10 patients had full range of motion, 3 had a flexion deficit of at least 30°, and 2 patients had residual instability of the medial collateral ligament. One postoperative superficial infection was noted. At the 3 month CT, 10 of 17 patients showed successful reduction without significant articular steps or anatomical malalignment.